Non-Performing Loans’ Impacts on the Banking Industries’ Loan Loss Provisions - Iskandar, Deni; Lumbantobing, Rudolf; Budianto, Tommy Wahyudi (International Dialogues on Education Journal, 2022)
Non-performing loans can impact the loan loss provisions of the banking industry. The sample of this research was collected from three banks: PT Bank Negara Indonesia (Persero) Tbk, PT Bank Rakyat Indonesia (Persero) Tbk, and PT Bank Mandiri (Persero) Tbk, for the period of 2013-2018. There were 72 data, 24 from each of the banks. The analysis was carried out using multiple linear regression and Sobel path analyses. The results showed that Capital Adequacy Ratio had a significant positive effect on Non-Performing Loans. Interest rates did not significantly affect Non-Performing Loans. Non-Performing Loans did not significantly affect Loan Loss Provision. Capital Adequacy Ratio had a significantly positive effect on Loan Loss Provision. Interest rates did not significantly affect Loan Loss Provision. Foreign exchange rates (USD against Rupiah) did not significantly moderate the positive effect of the Capital Adequacy Ratio on the Loan Loss Provision. USD exchange rates significantly moderated the negative effect of Non-Performing Loans on Loan Loss Provision. The interaction between the USD exchange rate and Non-Performing Loans negatively affected Loan Loss Provision. Foreign exchange rates did not significantly or positively moderate the effect of interest rates on Loan Loss Provision. Non-Performing Loans significantly mediated the positive effect of Capital Adequacy Ratio on the Loan Loss Provision. In other words, the positive effect of the Capital Adequacy Ratio on Loan Loss Provision is more positive when Non-Performing Loans increase, and vice versa. Non-Performing Loans did not significantly mediate the negative effect of interest rates on Loan Loss Provision, or the negative effect of interest rates on the Loan Loss Provision would be more negative when the Non-Performing Loans decreases, and vice versa.